2007
DOI: 10.1063/1.2712031
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced spin-dependent tunneling magnetoresistance in magnetite films coated by polystyrene

Abstract: Hematite films were deposited by magnetron sputtering. A phase transformation from hematite to magnetite occurred when polystyrene ͑PS͒ coated hematite films were annealed above 200°C in hydrogen flow. Giant negative magnetoresistance ͑MR͒ was observed with the best MR ratio of over 8% ͑at room temperature and in a field of 5.5 T͒ found in samples annealed at 230°C. The temperature dependence of the resistivity is characteristic of intergranular tunneling. After the PS layer was removed and the films annealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…This suggests that a simple directtunneling conductance mechanism cannot be a suitable explanation for such phenomena. In addition, no obvious transition is observed in the whole field range to distinguish the low-field MR and the high-field MR, which are found in composite granular system [6,10] In our case, the MR behavior is more like the spindependent scattering of electrons on the interfaces than the spindependent tunneling of electrons through the grain boundaries. In the high-field region, the MR value reaches to about 10% at 100 K, while decreases quickly to a small value of 3% at 300 K. The quick decrease of MR with temperature increasing is attributed to the spin-polarization loss during the increase of the inelastic-scattering process [1,6].…”
Section: Measurements and Analysismentioning
confidence: 61%
See 1 more Smart Citation
“…This suggests that a simple directtunneling conductance mechanism cannot be a suitable explanation for such phenomena. In addition, no obvious transition is observed in the whole field range to distinguish the low-field MR and the high-field MR, which are found in composite granular system [6,10] In our case, the MR behavior is more like the spindependent scattering of electrons on the interfaces than the spindependent tunneling of electrons through the grain boundaries. In the high-field region, the MR value reaches to about 10% at 100 K, while decreases quickly to a small value of 3% at 300 K. The quick decrease of MR with temperature increasing is attributed to the spin-polarization loss during the increase of the inelastic-scattering process [1,6].…”
Section: Measurements and Analysismentioning
confidence: 61%
“…In our sample, the MR ratio increases with the decrease of temperature above Verwey transition and then decreases below the transition. The drop of MR ratio below the Verwey point is probably attributed to the rapid increase in the resistivity of magnetite, which diminishes the spin-dependent scattering current [10].…”
Section: Measurements and Analysismentioning
confidence: 98%
“…Recently, some investigations have focused on improving MR performance of Fe 3 O 4 . [17][18][19][20][21][22] Zeng et al 17 reported 35% MR at 60 K for ordered three-dimensional arrays of Fe 3 O 4 nanoparticles with annealing in high vacuum. Rybchenko et al 19 showed enhancement in MR of bulk granular magnetite by annealing in paraffin wax.…”
Section: Introductionmentioning
confidence: 99%
“…17 Magnitude of the spin polarized current was found to depend on material microstructure, grain size, grain boundary, defects, strain effects, and surface/interface reconstruction. 18 Much of the research in this area is on oxides in the form of either bulk, compact powders, 15 epitaxial or continuous thin films, 19 epitaxial core-shell nanowires, 12 and more recently in the form of all oxide nanowires. 14 Magnetoresistance in these structures is credited to tunneling of spin-polarized electrons across the antiferromagnetically coupled antiphase/grain boundaries or interparticle contacts.…”
mentioning
confidence: 99%